Intracellular K+-Responsive Block Copolymer Micelles for Targeted Drug Delivery of Curcumin - Jiang, Mingyue; Chen, Le; Chen, Bo; Yu, Qinghua; Zhang, Xianming; Jing, Weihong; Ma, Limei; Deng, Tao; Yang, Zhangyou; Yu, Chao (Frontiers in Bioengineering and Biotechnology, 2022)
Curcumin (CUR) is a natural bioactive compound that has attracted attention as a “golden molecule” due to its therapeutic properties against several types of tumors. Nonetheless, the antitumor application of CUR is hampered due to its extremely low aqueous solubility and chemical instability. Herein, a novel type of CUR-loaded polymeric micelles with intracellular K+-responsive controlled-release properties is designed and developed. The polymeric micelles are self-assembled by poly (N-isopropylacrylamide-co-acryloylamidobenzo-15-crown-5-co-N, N-dimethylacrylamide)-b-DSPE (PNDB-b-DSPE) block copolymers, and CUR. CUR is successfully loaded into the micelles with a CUR loading content of 6.26 wt%. The proposed CUR-PNDB-DSPE polymeric micelles exhibit a significant CUR release in simulated intracellular fluid due to the formation of 2 : 1 ‘‘sandwich’’ host–guest complexes of 15-crown-5 and K+, which lead to the hydrophilic outer shell of micelles to collapse and the drug to rapidly migrate out of the micelles. In vitro, the B16F10 cell experiment indicates that CUR-PNDB-DSPE micelles exhibit a high cellular uptake and excellent intracellular drug release in response to the intracellular K+ concentration. Moreover, CUR-PNDB-DSPE micelles show high cytotoxicity to B16F10 cells compared to free CUR and CUR-PEG-DSPE micelles. The polymeric micelles with intracellular K+-responsive controlled release properties proposed in this study provide a new strategy for designing novel targeted drug delivery systems for CUR delivery for cancer treatment.